(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What was the situation of crime in Slovenia in 2020? Purpose: Crime is a very harmful activity in society. The purpose and goal of the research is to review the situation in this area and make suggestions for improvement. Method: Frequency statistics and the chi-squared test were used. These two statistical methods are relevant for this type of research. Results: Crime statistics are presented by demographic characteristics and by type of crime. Women are more likely to be victims of crime than men. The younger and older generations are more likely to be victims of crime than the middle generation. Organization: The results are important for the police, the courts, and the educational system. Society: Raising awareness of the issue throughout society is important. Only in this way we can improve the situation. Originality: The research is important for increasing security at the level of the whole society. Limitations/further research: Only data from 2020 was used. An in-depth quantitative and qualitative analysis is needed.